Calcium-dependent adhesion protein CDH18, a potential biomarker for prognosis in uterine corpus endometrial carcinoma - Tang, Xiaoxuan; Dang, Shanxing; Qiu, Jie; Zhou, Ruilan; Ling, Jing; Zhang, Limei; Peng, Xiaopeng; Li, Qingyun; Liu, Jin; Liao, Wei; Mei, Qingxiu; Xie, Miao; et al. (Frontiers in Molecular Biosciences, 2025)
BackgroundUterine corpus endometrial carcinoma (UCEC) is one of the most common cancers in women, yet lacks specific and sensitive tumor markers for diagnosis, as traditional markers like CA125 show limited specificity. This study investigates the clinical significance and prognostic value of CDH18, a calcium-dependent adhesion protein linked to tumor progression, in UCEC.MethodsClinical data from UCEC patients were sourced from The Cancer Genome Atlas (TCGA) database. Pan-cancer analysis, differential expression examination, and survival analysis were conducted to investigate the differential expression of the calcium associated protein-CDH18 and its prognostic relevance. CDH18 mutations in UCEC were examined using the cBioPortal database. Additional analyses included functional enrichment, tumor mutational burden, tumor microenvironment (TME) estimates via ESTIMATE, and immune infiltration assessment to clarify CDH18’s potential mechanisms in UCEC. Drug sensitivity testing was utilized to identify more suitable therapeutic options for patients. Immunofluorescence staining (IF) and Real-Time Polymerase Chain Reaction techniques (RT-PCR) confirmed CDH18 expression in UCEC tumor.ResultsCDH18 expression was markedly increased in UCEC and showed a significant association with poorer prognosis, which was confirmed by our IF and RT-PCR results. Thirteen mutation sites were identified, and survival analysis showed that patients with higher CDH18 expression had shorter overall survival. The expression of CDH18 was confirmed to be an independent predictor of overall survival by multivariate COX regression analysis. Additionally, a predictive nomogram model was developed to accurately forecast outcomes for individuals with UCEC. Correlation analysis revealed that CDH18 expression exhibited a negative correlation with CD8 T cell levels and a positive correlation with resting NK cell and macrophage M2 levels. In the group with high CDH18 expression, the IC50 values for (5Z)-7-Oxozeaenol, AG-014699, CEP-701, Mitomycin C, PD-0325901, PD-0332991, PHA-665752, SL 0101-1, and SN-38 were notably elevated.ConclusionCDH18 is a novel promising biomarker in UCEC, uniquely associating tumor progression, immune modulation, and chemotherapy resistance, offering enhanced prognostic accuracy and guiding individualized therapeutic strategies for improved patient outcomes.